Grappling with Cairo’s garbage: Informal sector integration as a means to urban sustainability - Bakry, Hussein (AUC Knowledge Fountain, 2015)
Sustainable waste management systems contribute to overall urban sustainability. In developing country cities such as Cairo, the informal sector plays a vital role in these systems, and policy to reform the waste sector must acknowledge that in order to achieve urban sustainability. Cairo is a city that is undergoing rapid urbanization with a rising population, putting strain on resources and public services. An increase in informal housing areas and jobs was only natural to accommodate the growing underclass within the city. One community that developed as a result was the zabbaleen. This community, most of which resides in Manshiet Nasser, took it upon itself to collect municipal waste and recycle it for economic gain. The result was a highly organized and efficient informal waste management system for the city that provided jobs and livelihoods for thousands of families. However, the policy to privatize the sector excluded this essential actor and focused much on ‘modernization’ and ‘proper’ disposal, taking a more linear approach to waste management. This resulted in a less efficient waste management system as the amount of material recycled dropped, which a) had negative socioeconomic implications on the thousands of families operating in the informal sector and b) visible environmental degradation due to waste accumulation. In order to build a more sustainable waste management, the successful integration of the informal sector in this case becomes a key issue. The problems with the currently implemented policy need to be thoroughly understood in order to devise a new policy that adequately addresses them. The government recently launched the National Solid Waste Management Program (NSWMP) to address these problems, acknowledging the need for informal sector integration. However, this is a program that is in the early stages of implementation and therefore requires continuous scrutiny. This thesis concluded that successful integration of the informal sector rests on three key factors: a) source segregation of waste, b) development of waste management entrepreneurship, and c) proper pricing of disposal. The new policy seems to account for these three factors, but it remains to be seen how they will be addressed in upcoming legislation governing the sector.